2017
DOI: 10.1121/1.4973412
|View full text |Cite
|
Sign up to set email alerts
|

Infant pitch perception: Missing fundamental melody discrimination

Abstract: Although recent results show that 3-month-olds can discriminate complex tones by their missing fundamental, it is arguable whether they are discriminating on the basis of a perceived pitch. A defining characteristic of pitch is that it carries melodic information. This study investigated whether 3-month-olds, 7-month-olds, and adults can detect a change in a melody composed of missing fundamental complexes. Participants heard a seven-note melody and learned to respond to a change that violated the melodic cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…It is believed that little children prefer mother singing than talking to them (Mithen 2009 ). Lau et al ( 2017 ) compared pitch perception in small groups of 3-months-old infants, 7-months-old babies and adults. The experiment has shown that 3-months-old infants were fully functional to discriminate the missing fundamental melodies.…”
Section: Absolute Pitchmentioning
confidence: 99%
“…It is believed that little children prefer mother singing than talking to them (Mithen 2009 ). Lau et al ( 2017 ) compared pitch perception in small groups of 3-months-old infants, 7-months-old babies and adults. The experiment has shown that 3-months-old infants were fully functional to discriminate the missing fundamental melodies.…”
Section: Absolute Pitchmentioning
confidence: 99%
“…The ability to discriminate pitch does not necessarily predict the ability to utilize it in the context of competing speech. Infants as young as 3 months can discriminate complex tones on the basis of their pitch (Lau & Werner 2012Lau et al 2017), and 4-to 6-montholds can discriminate voices of the same or different sex (Masapollo et al 2016). However, infants as old as 16 months of age do not appear to be able to use this information to detect speech in the presence of competing sounds Newman & Morini 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Since F 0 neural encoding has been suggested to report phonological, syntactic, and semantic cues, even in a nontonal language like English (Nakatani & Schaffer 1978), crucial information for language acquisition (He et al 2007; Lau et al 2017), the analysis was centered on the stimulus F 0 . F1 and F2 were not investigated because their frequencies were above 500 Hz, and a recent study has showed that no FFR signal could be detected in newborns for harmonics above this value (Arenillas-Alcón et al 2021), roughly corresponding to the frequency limits of the natural filter of the mother’s womb (Gerhardt & Abrams 2000; Lahav & Skoe 2014).…”
Section: Methodsmentioning
confidence: 99%